2005
DOI: 10.1161/01.hyp.0000175813.04375.8a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Functional Interaction of the Angiotensin-(1–7) Receptor Mas With AT 1 and AT 2 Receptors in the Mouse Heart

Abstract: Abstract-The aim of this study was to evaluate the angiotensin (Ang)-(1-7) effects in isolated mouse hearts. The hearts of male C57BL/6J and knockout mice for the Ang-(1-7) receptor Mas were perfused by the Langendorff method. After a basal period, the hearts were perfused for 20 minutes with Krebs-Ringer solution (KRS) alone (control) or KRS containing Ang-(1-7) (0.22 pmol/L), the Mas antagonist A-779 (115 nmol/L), the angiotensin type 1 receptor antagonist losartan (2.2 mol/L), or the angiotensin type 2 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
149
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(166 citation statements)
references
References 49 publications
12
149
1
4
Order By: Relevance
“…18 These findings suggest a functional and possibly physical interaction between Mas receptor and AT2R in the vascular system. 11 We found that Ang-(1-7) reduced expression of IL-1β and TNF-α in cerebral arteries. Both IL-1β and TNF-α have linked with the formation and progression of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…18 These findings suggest a functional and possibly physical interaction between Mas receptor and AT2R in the vascular system. 11 We found that Ang-(1-7) reduced expression of IL-1β and TNF-α in cerebral arteries. Both IL-1β and TNF-α have linked with the formation and progression of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 65%
“…7,9 Although the binding affinity of AT2R with Ang-(1-7) is relatively weak, AT2R appears to mediate some of the vascular effects of Ang- (1-7). 10,11,22 In spontaneously hypertensive rats, the vaso-suppressive effect of Ang-(1-7) appears to be dependent on the activation of AT2R. 10 The Mas receptor antagonist (A779) did not block the vaso-supressive effect of Ang-(1-7) in these rats.…”
Section: Discussionmentioning
confidence: 94%
“…Binding studies showed that Ang-(1-7) binds a receptor, which was completely blocked with the addition of D-Ala 7 -Ang-(1-7) (Tallant et al 1997), suggesting involvment of the mas receptor. Therefore, it is known that Ang-(1-7) binds the mas receptor and is a least partially responsible for the physiological effects reported for Ang-(1-7), but given the current data on interactions of the different angiotensin receptors (Castro et al 2005;Kostenis et al 2005), we do not even come close to understanding the roles of the angiotensin receptor types as they pertain to their physiological actions and/or interactions. The role of this newly reported Ang-(1-7) receptor remains to be elucidated, and its functional significance may bring scientists to a better understanding of how the system functions not only within itself, but also with other endogenous physiological systems.…”
Section: Pharmacodynamicsmentioning
confidence: 82%
“…In addition, the existence of a new ANG-(1-7) receptor subtype has been suggested [156], and an interaction between ANG-(1-7) and different ANG II receptors has also been proposed [157,158]. In hypertensive animals, ANG-(1-7)-induced vasodilation was restored by acute or chronic AT1 blockade with losartan, suggesting an interaction between AT1 and Mas [157][158][159].…”
Section: Other Receptorsmentioning
confidence: 99%
“…In hypertensive animals, ANG-(1-7)-induced vasodilation was restored by acute or chronic AT1 blockade with losartan, suggesting an interaction between AT1 and Mas [157][158][159]. Furthermore, the contribution of AT2 and bradykinin B2 receptor (BKR) to the vascular effects of ANG-(1-7) should not be disregarded, and they suggest the potential presence of crosstalk between BKR with Mas and AT2 [148,160,161].…”
Section: Other Receptorsmentioning
confidence: 99%